Feminisms in the maze of leftist leaders in Latin America. Reflections unfinished - Vargas, Virginia (2018)
The essay analyzes the processes driven by progressive governments in Latin America from a gender perspective and from human rights, focusing on relationships to expand democracy, human rights and gender agenda between the government and feminist movements.